Pengaruh Leverage, Growth Opportunity dan Kepemilikan Manajerial Terhadap Konservatisme Akuntansi - Maslikhatul Ilmiyah; Tumirin Tumirin (PROCEEDING UMSURABAYA, 2022)
This study aims to test empirically the effect of leverage, growth opportunity, and managerial ownership on accounting conservatism. This research was conducted in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the period 2017-2019. This research method is to use quantitative methods using secondary data in the form of corporate financial statements. The sampling method using purposive sampling method so that the sample used 100 samples. The data analysis technique used is multiple linear analysis. The results of this study indicate that leverage has no effect on accounting conservatism, growth opportunity has negative effect on accounting conservatism, and managerial ownership has positive effect on accounting conservatism.Keywords: Accounting; Accounting Conservatism;Growth Opportunity; Leverage; Managerial Ownership.